Employee surveillance and the modern workplace - PITESA, Marko (Institutional Knowledge at Singapore Management University, 2012)
Employee surveillance is rapidly becoming widespread in the modern workplace. The rise of information technologies is enabling the development of unprecedented methods of surveillance and employees as well as employers are now facing a need for a reassessment of the system of moral relations this phenomenon entails. This chapter provides an overview of the most widespread workplace surveillance methods and tries to identify the stakeholders and analyse the relations between them. Finally, the key findings of this ethical assessment are pointed out and guidelines for a morally responsible approach to workplace surveillance are proposed. The level of the analysis, in terms of the classification presented in Chapter two, is primarily the relation between a single company and its stakeholders. However, many of these concerns relate to fundamental societal principles and as such can only be fully appreciated if one takes into account the rootedness of business in overall societal dynamics.